Lightweight aerated metakaolin-based geopolymer incorporating municipal solid waste incineration bottom ash as gas-forming agent - Zhu, Weiping (2020)
In this study, incineration bottom ash is used as the gas-forming agent, to replace costly aluminum powder, in the production of lightweight aerated metakaolin geopolymer. Results show that gas generation capacity of incineration bottom ash is about 1/250 that of aluminum powder. Addition of incineration bottom ash remarkably increases the yield stress and viscosity of fresh pastes. As a result, incineration bottom ash aerated geopolymers possess smaller voids because higher yield stress of paste restricts expansion of gas bubble and higher viscosity of paste prevents bubble coalescence. The resulting incineration bottom ash aerated geopolymers show comparable properties to the control aluminum aerated geopolymers, with a density of as low as 860 kg/m3 and corresponding compressive strength of 5.5 MPa and thermal conductivity of 0.33 W/m-K. Incineration bottom ash thus can be considered as alternative gas-forming agent for lightweight aerated geopolymer production.